IMPROVING ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) THROUGH STRENGTHENING ORGANIZATIONAL CLIMATE AND PERSONALITY - Nancy Yusnita; Widodo Sunaryo; Sri Yulianti (Sosiohumaniora, 2021)
Many kinds of research on Organizational Citizenship Behavior (OCB) had generated findings that OCB is considered one of the main ways to increase organizations’ effectiveness. This study examines factors that have a relationship with OCB, namely, organizational climate and personality. This study was conducted among Primary School teachers at Cileungsi District, Bogor, Indonesia. The sample for the study consisted of 152 permanent teachers derived randomly from its population  which is 245 Primary School teachers. The study mainly utilized quantitative data (from questionnaires). Regression and correlational analysis were applied, with that the relationship among variables found. The findings revealed that the school organizational climate had a positive and significant relationship with OCB. Similarly, teachers’ personalities had a positive and significant relationship with OCB. Both school organizational climate and teachers’ personalities simultaneously had a strong positive and significant relationship with OCB. Further analysis was conducted to find out which indicators of those variables that had a dominant influence on OCB. Based on the indicator analysis results, this study proposed some recommendations toward Primary School Principals at Cileungsi District, Bogor to strengthen indicators of Organizational Climate and Personality that have a high coefficient of correlation with OCB. By strengthening those indicators it can be predicted will improve teachers’ OCB.